Stirring the Pot: A Response to Rothman’s Right of Publicity - Dogan, Stacey (The Columbia Journal of Law & the Arts, 2019)
Any commentary on Jennifer Rothman’s terrific book has to begin with a compliment to her extraordinary commitment to the right of publicity. For the uninitiated, her website, Rothman’s Roadmap to the Right of Publicity, provides a treasure trove of information about the right of publicity in each of the fifty states. Professor Rothman has also written several articles and a number of excellent amicus briefs in some of the most important right-of-publicity cases in recent years. Finally, this latest contribution—her book—harnesses this exhaustive research and presents it as a historical narrative that is comprehensive, thoughtful, and readable. This book will serve as required reading for scholars, lawyers, and historians trying to understand the history, foundations, and key attributes of this perplexing area of law. Despite my admiration for Professor Rothman and her work, I view the role of a commentator as stirrer of the pot; so, while I agree with much of what she says in her book and her talk, I am going to focus on three points where I have a somewhat different perspective: first, the relationship between “privacy” and “publicity;” second, the role of alienability; and finally, prognosis and cure—or why the right of publicity is so hard, and how we might restore balance to this unwieldy cause of action.